Transfer of Personal Data by E-Commerce Companies: A Study From The Perspective of Indonesian Personal Data Protection Laws - Marischa, Diva; Setianingrum, Reni Budi (Universitas Negeri Semarang, 2024)
In the era of globalization, the protection of personal data has become a critical issue in Indonesia, especially within the e-commerce sector. Cases of this nature underscore the significance of safeguarding personal data and enforcing stringent legal measures. This research employs a normative juridical legal study that integrates two primary approaches: the legislative approach and the comparative approach. The research data sources comprise primary, secondary, and tertiary legal materials obtained through a comprehensive literature review. The data analysis process is conducted using a descriptive method and applying deductive logic. The growth of e-commerce users in Indonesia has witnessed a significant increase. Law Number 27 of 2022 regulates the principles of personal data protection, encompassing the rights of data owners, transparency, and meticulous data management. While considered positive, a comparison with Malaysian regulations, such as the Personal Data Protection Act 2010, reveals fundamental differences that warrant attention. The implications of the regulation on the transfer of personal data in Law Number 27 of 2022 play a crucial role for e-commerce companies. They must ensure the security of consumers' personal data and adhere to legal principles to maintain consumer trust in an increasingly competitive market.